Augmented Reality for a New Reality: Using UTAUT-3 to Assess the Adoption of Mobile Augmented Reality in Tourism (MART) - Pinto, Agostinho Sousa (2022)
Few industries were more affected by the COVID-19 pandemic than tourism. One of Europe´s leading tourist destinations, Porto had undergone a major tourism boom until the start of pandemic. Mobile Augmented Reality (MAR) is one of the many emerging technologies that has great potential for tourist operators. Using this technology, they can create innovative tourism products that will help them recover from the present crisis. As a result, in this study, we will empirically test the latest version of the Unified Theory of Acceptance and Use of Technology (UTAUT) model to explore the factor leading to the adoption Mobile Augmented Reality in Tourism (MART) in Porto. In doing so, we aim to contribute to growing literature on the topic of Mobile Augmented Reality (MAR). The originality of this study lies in the use of an extended UTAUT model with greater predictive power and the exploration of the moderative role of gender, age and experience. To the data obtained from a random sample of 201 respondents who voluntarily answered an anonymous online questionnaire, we applied structural equational modeling and partial least squares (SEM-PLS) analysis to test the model. Our findings show that habit, hedonic motivations and facilitating conditions are the determinants of the use of MART.